Two new species of Rhiginia Stål, 1859, with taxonomical notes on species in the “cruciata-group” of this genus and an updated key to the New World genera of Ectrichodiinae (Heteroptera, Reduviidae) - Forthman, Michael; Gil-Santana, Hélcio R. (Zootaxa, 2021)
Taxonomical and morphological notes on the species in the “cruciata-group” of Rhiginia Stål, 1859 (Heteroptera, Reduviidae, Ectrichodiinae, Ectrichodiini) are provided. Photographs of the type specimens of R. bimaculata Breddin, 1914, R. cinctiventris (Stål, 1872), R. crucifera (Stål, 1872), and R. crudelis Stål, 1862 are presented. Rhiginia lourdesae sp. nov. and Rhiginia nicholsae sp. nov. are described based on male specimens from Mexico and considered as members of the “cruciata-group”. We also provide an updated key to the New World genera of Ectrichodiinae that includes the genus Tribelocodia Weirauch, 2010 to reflect recent taxonomic changes to the classification of the subfamily.